2023
DOI: 10.1073/pnas.2216524120
|View full text |Cite
|
Sign up to set email alerts
|

Overharvesting in human patch foraging reflects rational structure learning and adaptive planning

Abstract: Patch foraging presents a sequential decision-making problem widely studied across organisms—stay with a current option or leave it in search of a better alternative? Behavioral ecology has identified an optimal strategy for these decisions, but, across species, foragers systematically deviate from it, staying too long with an option or “overharvesting” relative to this optimum. Despite the ubiquity of this behavior, the mechanism underlying it remains unclear and an object of extensive investigation. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…ADHD-like cognitive phenotypes confer advantages or disadvantages depending on the environment. Foragers with ADHD-like traits may fare poorly in environments with multiple, learnable depletion rates (like the task used in [79]), by leaving patches before gathering enough information to learn the different patch types. In environments in which exhausted patches are renewed, primates are known to track renewal rates, such as the availability of fruit [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADHD-like cognitive phenotypes confer advantages or disadvantages depending on the environment. Foragers with ADHD-like traits may fare poorly in environments with multiple, learnable depletion rates (like the task used in [79]), by leaving patches before gathering enough information to learn the different patch types. In environments in which exhausted patches are renewed, primates are known to track renewal rates, such as the availability of fruit [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our task required participants to gather points—an abstract resource that stands in contrast to basic alimentary or other resources like calories. Nonetheless, animals and humans show similar patterns of behaviour that accord with foraging theory, whether foraging for resources in the real world or foraging for food pellets or points on a computer in the laboratory [22,50,55,79].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most general explanation—and one not exclusive of various other causes—is that rats were optimizing more than food earnings. In most scenarios foragers must consider many other factors while searching for food, including predation risk (Choi & Kim, 2010; Ydenberg & Dill, 1986), potential competitive or affiliative interactions with conspecifics (Li et al, 2012; Nagy et al, 2020; Whishaw, 1988; Whishaw & Tomie, 1988), energy expenditures (Hart et al, 2017), and opportunities for learning about aspects of their surroundings (Harhen & Bornstein, 2023; Wang & Hayden, 2021). Foraging strategies that balance these and other factors might depart from the predictions of rate maximization but nevertheless perform well in real-world scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The marginal value theorem (MVT) provides a means of computing the optimal patch residence time, which occurs when the rate of return from the current patch falls to the average rate of return over the environment as a whole (Charnov, 1976;Kolling & Akam, 2017;Stephens & Krebs, 1986). Previous studies have shown that the qualitative predictions of the MVT hold over a range of species, including humans (Constantino & Daw, 2015;Hall-McMaster et al, 2021;Harhen & Bornstein, 2023;Kolling et al, 2012), nonhuman primates (Barack et al, 2017;Blanchard & Hayden, 2015;Hayden et al, 2011;Turrin et al, 2017), and rodents (Kane et al, 2017(Kane et al, , 2019(Kane et al, , 2022Killeen et al, 1981;López-Yépez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, preferring familiarity can manifest as a form of perseverative information seeking that was associated with deprivation curiosity (Lydon-Staley, , a drive to reduce uncertainty and acquire missing information (Kashdan et al, 2018;. This preference for familiarity has been seen as prevalent in people with greater depressed mood and anxiety (Zhou et al, 2023), and may be an important heuristic strategy to reduce uncertainty for better reliability of future-oriented decisions (Harhen & Bornstein, 2023;Jiang, Kulesza, Singh, & Lewis, 2015). However, in large environments, such local heuristics are impoverished, particularly when higher-order associations are needed for planning.…”
Section: Introductionmentioning
confidence: 99%